Elderly deaths in Bursa, Turkey: a comprehensive forensic autopsy study - Özge Şener Malcı; Dilek Durak; Emir Bayram Malcı; Nursel Türkmen İnanır; Recep Fedakar (Egyptian Journal of Forensic Sciences)
Abstract Background In parallel with the increase in the elderly population, the proportion of elderly people in autopsies for forensic reasons is also increasing. This study aims to reveal the sociodemographic characteristics and causes of death of people aged 65 and over whose forensic autopsies were performed in Bursa, to compare the obtained data with the literature, and to draw attention to the importance of forensic autopsy in elderly death cases and the health and social problems of the elderly population. Results Four thousand two hundred forty-seven cases whose autopsies were performed in the 3-year period between 2019–2021 at the the Morgue Department of the Council of Forensic Medicine Bursa Group Administration were retrospectively scanned and 878 cases aged 65 and over were examined. It was determined that 20.6% of the 4247 cases who were autopsied were 65 years and over, the average age of the cases was 74.70 ± 7.3, and 74.6% were men. The most common cause of death was natural death, and cardiovascular diseases were found to be the most common cause of natural death. It has been determined that the most common accidents are traffic accidents in men and drowning in women. It was determined that 81.3% of suicide cases were committed by hanging, and hanging was the most common method of suicide in both genders. Conclusions We think that the information obtained from autopsy studies and determining the causes and origins of death will help determine the priorities for the necessary health services and social care for the elderly population in order to eliminate preventable causes.